Management by processes and administrative procedures for pension of survivors of the Peruvian Army - Berlanga Vera, Blas Jackson (2022)
The objective of this research is to define the way in which process management has a positive impact on the improvement of administrative procedures for pensions of survivors of official and non-commissioned officers of the Peruvian Army, contributing to the adequate administration of public management. A descriptive, correlational and explanatory methodology was applied; Likewise, among the research techniques and methods uses, we have the non-experimental, transversal correlational type. In addition, surveys, questionnaires and direct observation were used as research instruments that were applied to the heads of areas, relatives of officers and non-commissioned officers of the Peruvian Army. This research used a sample of 113 people; of which seven corresponded to the area heads of survivor pension procedures and 106 to the relatives of officers and non-commissioned officers of the Peruvian Army. The results of the investigation determined that the administrative procedures register improvements when process management is applied, facilitating customer satisfaction, the efficient management of operating costs, the variety of services and time, as well as its quality. The study concluded that process management positively influences administrative procedures; being essential to promote effective and efficient management of public administration.